A comperative review of Harrasment law and Islamic jurisprudence - Dr. Qammar Aziz; Dr. Muhammad Waris; Dr.Zia Ud Din (Journal of Religion and Society, 2025)
Getting someone to do something by intimidating or threatening to kill them; for example, having illicit sexual relations with them, getting them married, getting them divorced, or underestimating them falls under the category of personal harassment, which is a crime in law and has also been called illegal in Islamic jurisprudence; however, Paksitani law has issued punishment for it. Such incidents are happening in abundance in the modern era; researching them is a necessary of this era. And no significant work has been done on this topic, so this article has researched this topic. Keywords: Harassment, punish, law.